Introduction to the relativity principle - Barton, G. (Gabriel) (Chichester : John Wiley and Sons, 1999)
This book is divided into four parts: Introductory; Kienematics; Momentum and energy; Waves; ...
Keywords: Physics; Relativity; Relativity (Physics)